2017
DOI: 10.1021/acs.joc.7b00863
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Structure of the Antitubercular Natural Product Eucapsitrione?

Abstract: 1,5,7-Trihydroxy-6H-indeno[1,2-b]anthracene-6,11,13-trione (1), proposed to be the antitubercular natural product eucapsitrione, has been synthesized in 43% overall yield and six steps, including a key Suzuki-Miyaura biaryl coupling and a directed remote metalation (DReM)-initiated cyclization. The physical and spectroscopic properties of 1 do not match the data reported for the natural product. At this time there is insufficient information available to enable a structure reassignment. During the optimization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 95 publications
(154 reference statements)
1
7
0
Order By: Relevance
“…The mechanism of these antibacterial agents involves enhanced ROS generation and is followed by apoptotic cell death [6,7]. A number of compounds with a 1,4-naphthoquinone moiety can activate noticeable biological inhibitions such as antimicrobial [8], anticancer [9], antitubercular [10], antimalarial [11] and trypanocidal [12] activities. Due to the ability to generate ROS, naphthoquinone analogues are extremely cytotoxic to the infected cells and can restrict cellular enzymes, which are responsible for apoptosis and cell growth [13].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of these antibacterial agents involves enhanced ROS generation and is followed by apoptotic cell death [6,7]. A number of compounds with a 1,4-naphthoquinone moiety can activate noticeable biological inhibitions such as antimicrobial [8], anticancer [9], antitubercular [10], antimalarial [11] and trypanocidal [12] activities. Due to the ability to generate ROS, naphthoquinone analogues are extremely cytotoxic to the infected cells and can restrict cellular enzymes, which are responsible for apoptosis and cell growth [13].…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Notably,1 ,4-naphthoquinonesg raftedw ith an amino or substituted amino group at the 2-position have been potential candidates in medical and biological applications. Furthermore, recent researchh as demonstrated that these molecules exhibit antitubercular, [6] antimalarial, [7] trypanocidal, [8] anticancer, [9] and antimicrobial [10] activities.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] 1,4-Naphthoquinones and its related compounds are well-established for irreversible complexation during ROS generation in proteins, which leads to loss of protein function. [9] Due to these properties, 1,4-naphthoquinone derivatives exhibit biological properties such as antimicrobial, [10] antimalarial, [11] antitubercular, [12] anticancer, [13] and trypanocidal [14] activities.…”
Section: Introductionmentioning
confidence: 99%